The Eight Graders’ Perception of Speaking Online Learning During Covid-19 Pandemic in SMP at Misykat Al-Anwar - Khofifah Indah Hasanah; Sakhi Herwiana (Journal of Language Education (JoLE), 2023)
This research is based on online English learning that has been running for more than 1 year of class VIIIC junior high school student Misykat Al-Anwar most students complain that teaching and learning activities are very boring. Moreover, speaking skills require a lot of practice so that students are fluent in English. But with the Covid-19 pandemic, all learning activities are carried out online. Problems of this research how are the perception of VIIIC class students about English learning conducted online as well as its advantages and disadvantages. The researcher use the qualitative method. In accordance with the observations made students experience a lot of material that is not delivered, they feel monotonous, and also the network signal is inadequate for smooth learning.